Coherent Electron Positron Pair Production of Type-B in Crystals; 16th HiSOR Meeting on Coherent Radiation by High-energy Electrons, 13 March 1992, Hiroshima, Japan - Andreyashkin M. Yu.; Kunashenko Yu. P. Yuriy Petrovich; Pivovarov Yu. L. Yuriy Leonidovich; Zabaev V. N. Viktor Nikolaevich (1992, 1992)
В фонде НТБ ТПУ отсутствует